2014
DOI: 10.1186/1756-3305-7-166
|View full text |Cite
|
Sign up to set email alerts
|

Increase in number of helminth species from Dutch red foxes over a 35-year period

Abstract: BackgroundThe red fox (Vulpes vulpes) is host to a community of zoonotic and other helminth species. Tracking their community structure and dynamics over decades is one way to monitor the long term risk of parasitic infectious diseases relevant to public and veterinary health.MethodsWe identified 17 helminth species from 136 foxes by mucosal scraping, centrifugal sedimentation/flotation and the washing and sieving technique. We applied rarefaction analysis to our samples and compared the resulting curve to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 29 publications
8
42
1
Order By: Relevance
“…recent unpublished observations by local vets reporting chronic respiratory signs associated with a lung pattern compatible with angiostrongylosis suggest that the area is endemic for A. vasorum. The red fox (Vulpes vulpes) could be responsible for the introduction and spreading of the parasite as recently described in The Netherlands [26]. Clearly, additional studies in both final and intermediate hosts as well as proper information of practitioners regarding diagnosis and treatments are needed taking into account that highly effective drugs such as fenbendazole [27], moxidectin [27,28] and milbemycin oxime [29,30] are widely available.…”
Section: Discussionmentioning
confidence: 99%
“…recent unpublished observations by local vets reporting chronic respiratory signs associated with a lung pattern compatible with angiostrongylosis suggest that the area is endemic for A. vasorum. The red fox (Vulpes vulpes) could be responsible for the introduction and spreading of the parasite as recently described in The Netherlands [26]. Clearly, additional studies in both final and intermediate hosts as well as proper information of practitioners regarding diagnosis and treatments are needed taking into account that highly effective drugs such as fenbendazole [27], moxidectin [27,28] and milbemycin oxime [29,30] are widely available.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, prevalence around 40 % or higher have been found in different epidemiological studies. For example the prevalence in Slovenia was 58.9 % (Vergles Rataj et al, 2013), in Denmark 54.4 % or 84.1 % respectively (Al-Sabi et al, 2013;Franssen et al, 2014), and in Lithuania 76.9 % (Bružin-skaitė- Schmidhalter et al, 2012). Previous studies from the other regions of Italy reported a prevalence of 39.1 % of infected foxes among 129 examined in Tuscany (Magi et al, 2009), and 51.3 % of 645 foxes in northern Italy (and specifi cally in the regions Aosta Valley, Lombardy, Trentino Alto Adige and Veneto) (Di Cerbo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…6.5 (4.1-9.0) 2 (Jonas & Hahn, 1984;Jonas & Dräger, 1998) 33.8 (-) 1 (Jonas & Dräger, 1998) Saarland 25.6 (19.9-31.3) 2 (Ahlmann, 1996, Meine & Müller, 1996 No data Enge, 1996) No data Schleswig-Holstein 0.2 (0.0-0.4) 3 (Lucius et al, 1988;Nebel, 1996) 0.0 (-) 1 (Manke & Stoye, 1998) (Soldati et al, 1976;Rossi et al, 1983 ;Poglayen et al, 1985 ;Leoni et al, 1986;Iori et al, 1990 ;Guberti & Poglayen, 1991) 0.0 (0.0-0.0) 3 (Di Cerbo et al, 2008;Calderini et al, 2009;Magi et al, 2009) (Ahlmann, 1996;EFSA, 2006;EFSA, 2007;EFSA, 2013a; EFSA, 2015a) Netherlands 0.0 (-) 1 (Borgsteede, 1984) 9.4 (0.7-59.5) 3 (Takumi et al, 2008;Van der Giessen et al, 2004;Van der Giessen et al, 1998;Franssen et al, 2014;Maas et al, 2014) Poland 2.6 (-) 1 (Malczewski et al, 1999) (data until 1998) 15.1 (1.0-20.1) 8 (Borecka et al, 2008;Karamon et al, 2008;Karamon et al, 2011;Borecka et al, 2007;Malczewski et al, 2008;Borecka et al, 2009;Pacon et al, 2006;Karamon et al, 2014 (Ewald & Eckert, 1993;Alther, 1996) 48.5 (44.3-52.7) 2 (Hofer et al, 2000;…”
Section: Countrymentioning
confidence: 99%